Seeking new paradigms in Aboriginal education research: methodological opportunities, challenges and aspirations - Marnee Shay (Historia Social y de la Educación, 2016)
It is only relatively recently that Aboriginal peoples in Australia are represented in the academe, creating knowledges that speak for, and not of us. Internationally renowned Maori scholar, Professor Linda Tuhiwai Smith, was groundbreaking in her use of critical discourses needed for indigenous peoples globally to reclaim our knowledges and experiences through research. The emergence of Aboriginal and Torres Strait Islander scholars in Australia presents hope and opportunities for our communities to utilise the possibilities that ethical, Indigenous-driven research can have in interrogating complex and ongoing issues created by colonialism.